1995
DOI: 10.1039/c39950001355
|View full text |Cite
|
Sign up to set email alerts
|

Filling carbon nanotubes with small palladium metal crystallites: the effect of surface acid groups

Abstract: The filling of carbon nanotubes with palladium metal crystallites is described and it is shown that when the carbon nanotube samples are opened using nitric acid, surface acid groups (C02H and OH) are present on both the nanotubes and nanoparticles and these interact strongly with palladium ions: ultrasound pre-treatment of the carbon nanotube samples prior to the oxidation with nitric acid increases the number of these groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(50 citation statements)
references
References 7 publications
1
49
0
Order By: Relevance
“…Liquid phases, which may be high-temperature molten materials, aqueous solutions, or organic solutions, can be sucked into the inner cavities of CNTs provided that the filling liquids have relatively low surface tension, below a cut-off value at 100-200 mN/m [8,9]. The results have indicated that these procedures inevitably result in the deposition of a certain amount of materials onto external walls of the CNTs [5]. To achieve exclusive filling of CNTs, a simple strategy is suggested, illustrated in Fig.1.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Liquid phases, which may be high-temperature molten materials, aqueous solutions, or organic solutions, can be sucked into the inner cavities of CNTs provided that the filling liquids have relatively low surface tension, below a cut-off value at 100-200 mN/m [8,9]. The results have indicated that these procedures inevitably result in the deposition of a certain amount of materials onto external walls of the CNTs [5]. To achieve exclusive filling of CNTs, a simple strategy is suggested, illustrated in Fig.1.…”
Section: Introductionmentioning
confidence: 94%
“…1, the following inequality is needed: ΔE capillarity < Δ Esolvation < 0 The above inequality suggests that the impregnating solution and washing medium should be carefully chosen such that the impregnating solution should present limited solubility in the washing medium. Green and coworkers found that washing the CNTs which were filled by aqueous solutions of inorganic compounds in water removed almost all materials from both inside and outside of the tubes [3,5]. However, organic solvents, such as chloroform and benzene, are completely immiscible with CNTs impregnated with aqueous solutions and will not remove any excess precursor solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These functional groups were very important to further functionalize CNTs. Sonication could also produce defects on the sidewall of CNTs that were eager for further chemical reactions [103][104][105][106].…”
Section: Defect Functionalizationmentioning
confidence: 99%
“…About 15 mg of each non-loaded raw, oxidized and opened DWCNTs were loaded in solution with an excess of chloroquine diphosphate salt [29,30]. This anti-malarial drug is very soluble in water (100 mg mL -1 ) and extremely sensitive to sunlight.…”
Section: Chloroquine Loading Of Dwcntsmentioning
confidence: 99%